2007
DOI: 10.2353/ajpath.2007.060219
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Endotoxic Shock as a Consequence of Reduced Nitrosative Stress in MLCK210-Null Mice

Abstract: This study investigated the consequences of deletion of the long isoform of myosin light chain kinase (MLCK210) on the cardiovascular changes induced by the bacterial endotoxin lipopolysaccharide (LPS) and cecal ligation puncture using MLCK210 ؊/؊ mice. Here, we provide evidence that deletion of MLCK210 enhanced survival after intraperitoneal injection of LPS or cecal ligation puncture. LPS-induced vascular hyporeactivity to vasoconstrictor agents was completely prevented in aorta from MLCK210 ؊/؊ mice. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Thus, as opposed to the response of their wild‐type counterparts, the absence of oxidative stress under IH exposure in nmMLCK −/− mice could contribute to the conservation of vascular properties. Interestingly, this result is in accordance with a previous study describing the same protective effect of nmMLCK deletion on vascular oxidative stress in a model of lipopolysaccharide‐induced sepsis 20. We further demonstrated that nmMLCK inhibition abolishes the IH‐induced endothelial barrier dysfunctions, which could directly result from the prevention of oxidative stress47 and could explain the limitation of inflammation in the vascular wall of nmMLCK −/− compared with nmMLCK +/+ mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, as opposed to the response of their wild‐type counterparts, the absence of oxidative stress under IH exposure in nmMLCK −/− mice could contribute to the conservation of vascular properties. Interestingly, this result is in accordance with a previous study describing the same protective effect of nmMLCK deletion on vascular oxidative stress in a model of lipopolysaccharide‐induced sepsis 20. We further demonstrated that nmMLCK inhibition abolishes the IH‐induced endothelial barrier dysfunctions, which could directly result from the prevention of oxidative stress47 and could explain the limitation of inflammation in the vascular wall of nmMLCK −/− compared with nmMLCK +/+ mice.…”
Section: Discussionsupporting
confidence: 92%
“…In endothelial cells, this retraction is linked to endothelial permeability enhancement and vascular leakage under proinflammatory conditions. In this context, an activation of the nmMLCK has been linked to several pathophysiological conditions, such as vascular inflammation and atherosclerosis,18 acute lung injury,19 endotoxic shock,20 and severe burns 21…”
Section: Introductionmentioning
confidence: 99%
“…Activated NF-κB p65 may bind to the myosin light-chain kinase (MLCK) promoter region and increase MLCK expression [33,34]. MLCK-mediated MLC phosphorylation has been found to result in the contraction of actin-myosin filaments, altering TJ protein localization and expression as well as TJ barrier functional openings [35]. The results presented here showed that C-BF markedly inhibited NF-κB activation which may suppress the activation of MLCK and reduce the disruption of TJs.…”
Section: Discussionmentioning
confidence: 72%
“…or i.p. injection of LPS, which on its own reproduces many of the features of gram-negative sepsis (19,120). This model induces endotoxemia, is very acute, enables precise dosing, and is highly reproducible, but no infection is involved, which makes the model somewhat less relevant to sepsis in humans.…”
Section: Mouse Models For Studying Infection Sepsis and Septic Shockmentioning
confidence: 99%